A mediação da leitura em libras para crianças surdas nas séries iniciais do ensino fundamental: o caso do Instituto Felipe Smaldone - IGREJA, Rosana do Socorro Corrêa (2017)
This paper discusses and investigates the issue of reading mediation in Brazilian Sign Language in the early grades of elementary school, whose specific objectives are to identify those professionals who promote encourage reading; also identify what are the techniques and or resources used and also analyze deaf children how they interact in the process and if they like this activity. The literature brings concepts of mediation of information as an object of study of Information Science, the Deafness Children and their classification, a brief history of POUNDS as nº5626 decree of December 22, 2005, which regulated by Law No. 10.246 of 24 April 2002, recognized as the first language of the deaf, and also on the Children's books translated into pounds. The research subjects were the teachers and deaf children in the early grades; the methodology used for this research was through observations in the field and application of open and closed questionnaires to the subjects involved in the research. Data analysis revealed that the institution has professional relevantly qualified in pounds, to make reading mediation use dactylology, but found the lack of materials translated into pounds, as printed books and digital materials and also a specific school library with a qualified librarian in sign language, so that it can interact with the student (a), thus will contribute to the integration and inclusion of it.